A Non-Randomized clinical study to observe the efficacy of Individualized Homoeopathic medicine in the management of Melasma using Synthesis Repertory - Bhartiya, Dr. Nitisha Manoj; Sheth, Dr. Priya Rohit (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Melasma is a recurrent, chronic hyperpigmentation disorder caused by hyperactive melanocytes leading to excessive melanin deposition in the epidermis and dermis. It commonly presents as marginated facial hyperpigmentation and significantly affects psychological well-being and quality of life. Research on its psychological burden and management in India remains limited. Homoeopathy, with its holistic and individualized approach, may provide therapeutic benefit where conventional treatments show limitations. Methods: A single-blind, prospective, non-randomized clinical study was conducted at the OPD of Bharati Vidyapeeth (Deemed to be University) Homoeopathic Medical College and Research Centre, Pune. Thirty patients aged ≥25 years were enrolled and completed follow-up. Individualized homoeopathic medicines were prescribed using the Synthesis Repertory. Outcomes were assessed using the Melasma Severity Index (MSI) and Melasma Quality of Life (MelasQoL) scales before and after intervention. Wilcoxon signed-rank test and paired t-test were applied. A p-value
Keywords: Melasma; Homoeopathy; Melasma Severity Index; Melasma Quality of Life; Synthesis Repertory; Quality of life